A parametrization of subgrid orographic rain enhancement via the seeder–feeder effect. (15th September 2015) - Smith, S. A.; Field, P. R.; Vosper, S. B.; Shipway, B. J.; Hill, A. A.
Abstract : Numerical models used for low‐resolution weather and climate simulations are unable to produce enough orographic rain enhancement via the seeder–feeder effect during the passage of frontal systems when the orography is not sufficiently well represented. This article describes the development of a simple parametrization scheme to remedy this problem. The scheme estimates the increase in the grid‐box mean cloud liquid‐water mixing ratio that would result from vertical displacements produced by unresolved hills, accounting for regions where the actual surface is both higher and lower than the model surface. Using idealized two‐dimensional simulations of neutrally stratified flow over a Gaussian‐shaped ridge resolved to varying degrees, the new scheme was shown to increase the total (resolved plus parametrized) orographic water towards that produced over a well‐resolved hill, with good agreement for a wide range of hill sizes. This subgrid orographic water can be used by a microphysics parametrization scheme to enhance the growth of rain (or snow) via accretion. In simulations with a constant rain rate into the top of the domain, the surface orographic rain rate was increased over a small completely subgrid hill by up to 90%, giving much better agreement with the simulations over a well‐resolved hill. The scheme also increases the rain produced by flow over large subgrid mountains if the resolved cloud is able to produce some rain via autoconversion.